Oncolytic virus treatment differentially affects the CD56dim and CD56bright NK cell subsets in vivo and regulates a spectrum of human NK cell activity. Issue 1 (9th March 2022) - Wantoch, Michelle; Wilson, Erica B.; Droop, Alastair P.; Phillips, Sarah L.; Coffey, Matt; El‐Sherbiny, Yasser M.; Holmes, Tim D.; Melcher, Alan A.; Wetherill, Laura F.; Cook, Graham P.
Abstract: Natural killer (NK) cells protect against intracellular infection and cancer. These properties are exploited in oncolytic virus (OV) therapy, where antiviral responses enhance anti‐tumour immunity. We have analysed the mechanism by which reovirus, an oncolytic dsRNA virus, modulates human NK cell activity. Reovirus activates NK cells in a type I interferon (IFN‐I) dependent manner, inducing STAT1 and STAT4 signalling in both CD56 dim and CD56 bright NK cell subsets. Gene expression profiling revealed the dominance of IFN‐I responses and identified induction of genes associated with NK cell cytotoxicity and cell cycle progression, with distinct responses in the CD56 dim and CD56 bright subsets. However, reovirus treatment inhibited IL‐15 induced NK cell proliferation in an IFN‐I dependent manner and was associated with reduced AKT signalling. In vivo, human CD56 dim and CD56 bright NK cells responded with similar kinetics to reovirus treatment, but CD56 bright NK cells were transiently lost from the peripheral circulation at the peak of the IFN‐I response, suggestive of their redistribution to secondary lymphoid tissue. Coupled with the direct, OV‐mediated killing of tumour cells, the activation of both CD56 dim and CD56 bright NK cells by antiviral pathways induces a spectrum of activity that includes the NK cell‐mediated killing of tumour cells and modulation of adaptive responses via the trafficking of IFN‐γ expressing CD56 bright NK cells to lymph nodes. Abstract : Oncolytic reovirus treatment activates NK cells via a type I interferon‐dependent mechanism that modulates human NK cell activity in vitro and in vivo.